Understanding internet-only bank service adoption: An integration of the unified technology theory of acceptance and innovation resistance model - Daewon Kim; Jae Kwon Bae (Global Business & Finance Review (GBFR), 2020)
Purpose: To explain the innovation resistance and consumer acceptance of internet-only bank services, this paper proposes an integrated research model that builds on the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) and Innovation Resistance Model (IRM).We aim to identify the factors that influence the innovation resistance and consumer acceptance for internet-only bank services. Design/methodology/approach: The performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation of UTAUT2 and the personal innovativeness and perceived security of IRM were adopted in the model.To this end, 203 online survey responses from non-users of internet-only bank services were collected and analyzed. Findings: We find that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, personal innovativeness, and perceived security affected innovation resistance that in turn ultimately has a negative influence on the consumer acceptance of internet-only bank services. Research limitations/implications: Our sample consists of a homogenous age group, college students whose age are between 20 and 30 years old.For a more robust test and results and as internet-only banking become wide-spread, a future study should include a diverse age group which properly represents internet-only bank service users. Originality/value: Theoretically, we propose an integrated research model that combines UTAUT2 and IRM.The proposed research model adds variables related to personal innovation and security that could not be explained in UTAUT2.Specifically, this study identify factors that have significant effect on user acceptance or resistance for internet-only bank services.Thus, we highlight factors that can promote market activation and use intention of internet-only bank services.These are expected to be useful to internet-only bank operators and business model developers.
Keywords: 650; Internet-only Banks; Extended unified theory of acceptance and use of technology; Innovation resistance model